Drop coating deposition Raman spectroscopy as a potential tool for identification and determination of fructose in seminal plasma. (12th September 2014) - Huang, Zufang; Wang, Jing; Lin, Jinyong; Chen, Xiwen; Sun, Yan; Cao, Gang; Lin, Juqiang; Lei, Jinping; Lin, Hongxin; Chen, Rong
<x xml:space="preserve">Abstract</x> The detection of fructose in the seminal plasma has significant value to evaluate the function of seminal vesicles and evaluate male fertility. In this study, drop coating deposition Raman (DCDR) method was utilized to quantitative determination of fructose in seminal plasma. Optimization of experimental parameters to achieve reagent‐free and rapid detection of fructose was also investigated. Different fructose concentrations within physiological level demonstrated a linear relationship with the band intensity of 627 cm−1 (assigned to fructose), and the relative error of predicted fructose concentration was 10.23%. Our results show that DCDR method has the potential for the determination of fructose concentration. Copyright © 2014 John Wiley & Sons, Ltd.